Brassica Species in Phytoextractions: Real Potentials and Challenges - Tijana Zeremski (MDPI AG, 2021)
The genus Brassica is recognized for including species with phytoaccumulation potential and a large amount of research has been carried out in this area under a variety of conditions, from laboratory experiments to field trials, with spiked or naturally contaminated soils, using one- or multi-element contaminated soil, generating various and sometimes contradictory results with limited practical applications. To date, the actual field potential of Brassica species and the feasibility of a complete phytoextraction process have not been fully evaluated. Therefore, the aim of this study was to summarize the results of the experiments that have been performed with a view to analyzing real potentials and limitations. The reduced biomass and low metal mobility in the soil have been addressed by the development of chemically or biologically assisted phytoremediation technologies, the use of soil amendments, and the application of crop management strategies. Certain issues, such as the fate of harvested biomass or the performance of species in multi-metal-contaminated soils, remain to be solved by future research. Potential improvements to current experimental settings include testing species grown to full maturity, using a greater amount of soil in experiments, conducting more trials under real field conditions, developing improved crop management systems, and optimizing solutions for harvested biomass disposal.